2014
DOI: 10.1055/s-0034-1383502
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Digital Wireless Technology for Persons with Hearing Aids

Abstract: Wireless technology for persons with hearing loss began with cumbersome body-worn systems that nevertheless provided speechrecognition benefits in noisy environments. The first ear-level wireless systems were welcomed despite the awkward antenna that extended from the behind-the-ear case. The next-generation, removable, multichannel receiver provided a cost-effective means for school districts to maintain a stock of equipment to be used across students and classrooms. More recently, the advances have been less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 7 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Published studies have suggested several possible interventions for patients with abnormal auditory abilities, including compensatory strategies, counseling, and auditory training [ 13 ]. Several studies suggest that technologies that increase the signal-to-noise ratio (SNR), such as low- (or mild-) gain hearing aids (LGHAs), with or without the use of remote microphones, can provide significant benefits to those with SHDs and NHTs [ 14 , 15 , 16 , 17 ]. Anecdotal results from military audiologists have reported positive results from the use of LGHAs (i.e., self-reported satisfaction and use through data logging), and many military clinics have started routinely prescribing LGHAs to patients who present with SHDs and NHTs.…”
Section: Introductionmentioning
confidence: 99%
“…Published studies have suggested several possible interventions for patients with abnormal auditory abilities, including compensatory strategies, counseling, and auditory training [ 13 ]. Several studies suggest that technologies that increase the signal-to-noise ratio (SNR), such as low- (or mild-) gain hearing aids (LGHAs), with or without the use of remote microphones, can provide significant benefits to those with SHDs and NHTs [ 14 , 15 , 16 , 17 ]. Anecdotal results from military audiologists have reported positive results from the use of LGHAs (i.e., self-reported satisfaction and use through data logging), and many military clinics have started routinely prescribing LGHAs to patients who present with SHDs and NHTs.…”
Section: Introductionmentioning
confidence: 99%